2020
DOI: 10.32535/ijabim.v5i3.977
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Consumers’ Choice of Laundry Services in Manado City: An Empirical Study

Abstract: Lifestyle, including activities, interests, and opinions, influences consumer shopping behaviour and decisions in laundry businesses. It relates to individual’s way of life, use of money and time, expressed in activities, interests, and opinions. Therefore, those partaking in this business need to understand their consumers’ lifestyle, for complete information on what products to offer, innovate, and promote. This study was conducted in Malalayang, Paal 2, Boulevard, and the areas surrounding Sam Ratulangi Air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Lifestyle has a considerable impact on purchasing decision variables Kaligis, 2020). Two people of the same age, income, education, and career do not have to live their lives in the same way (Dermawan, 2021).…”
Section: Lifestylementioning
confidence: 99%
“…Lifestyle has a considerable impact on purchasing decision variables Kaligis, 2020). Two people of the same age, income, education, and career do not have to live their lives in the same way (Dermawan, 2021).…”
Section: Lifestylementioning
confidence: 99%
“…To survive in the competitive market, they need to establish a new business model that represents their unique image, such as concentrating on consumer needs, product creativity to increase or maintain target customers. Kaligis, (2020) suggested that technological advance would lead to the development of agriculture in which economic changes, cultural transformations, technology and information can change lifestyles, thereby changing expected decisions.…”
Section: Introductionmentioning
confidence: 99%